Risk Stratification for Proven Acute Pulmonary Embolism: What Information Is Needed? - Barrios, Deisy; Yusen, Roger D.; Jiménez, David (Seminars in Respiratory and Critical Care Medicine, 2017)
Classification of risk drives treatment decisions for patients with acute symptomatic pulmonary embolism (PE). High-risk patients with acute symptomatic PE have hemodynamic instability (i.e., shock or hypotension present), and treatment guidelines suggest systemically administered thrombolytic therapy in this setting. Normotensive PE patients at low risk for early complications (low-risk PE) might benefit from treatment at home or early discharge, while normotensive patients with preserved systemic arterial pressure deemed as having a high risk for PE-related adverse clinical events (intermediate–high-risk PE) might benefit from close observation and consideration of escalation of therapy. Prognostic tools (e.g., clinical prognostic scoring systems, imaging testing, and cardiac laboratory biomarkers) assist with the classification of patients into these categories.
Keywords: pulmonary embolism; prognosis; mortality